1992
DOI: 10.1287/isre.3.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Building an Information System Design Theory for Vigilant EIS

Abstract: This paper defines an information system design theory (ISDT) to be a prescriptive theory which integrates normative and descriptive theories into design paths intended to produce more effective information systems. The nature of ISDTs is articulated using Dubin's concept of theory building and Simon's idea of a science of the artificial. An example of an ISDT is presented in the context of Executive Information Systems (EIS). Despite the increasing awareness of the potential of EIS for enhancing executive str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
1,025
0
30

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,097 publications
(1,061 citation statements)
references
References 22 publications
6
1,025
0
30
Order By: Relevance
“…Following Walls, Widmeyer, and El Sawy's (1992) information system design theory (ISDT), availability and portability system features as meta-designs that support organizational requirements as meta-requirements were proposed to form the base of the system-level investigation of this study. A meta-analysis of other system features is covered in the Appendix, however, these features are beyond the scope of this paper.…”
Section: Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Following Walls, Widmeyer, and El Sawy's (1992) information system design theory (ISDT), availability and portability system features as meta-designs that support organizational requirements as meta-requirements were proposed to form the base of the system-level investigation of this study. A meta-analysis of other system features is covered in the Appendix, however, these features are beyond the scope of this paper.…”
Section: Frameworkmentioning
confidence: 99%
“…In the methodology section, the meta-kernel is embedded into the metarequirements following information systems design theory as presented in Walls et al (1992).…”
Section: Design Of An Instrumentmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of the two studies will be presented and discussed, before moving on to a more general set of reflections on the design science program, motivated by recent debate over its nature and agenda (Chatterjee and Hevner 2006;Hevner et al 2005). As an instance 2 Design theory falls into two broad categories (Venable 2006;Walls et al 1992): knowledge about the design of products and about the design process itself, corresponding to the two senses of design as noun and verb. Both categories are relevant here; we are interested in the design of complex information systems and also the methodology of design.…”
Section: Research Aims and Overviewmentioning
confidence: 99%
“…Van Houwelingen and Van Raaij (1989) showed that goal-setting in conjunction with feedback (a novel "energy cost indicator") produced a significant reduction in energy consumption. tradition with a lineage reaching back over many years (e.g., March and Smith 1995;Markus et al 2002;Walls et al 1992), IS design research remains a minority genre. This is as true for the deliberations of IFIP WG8.6 as it is for the field in general.…”
Section: Introductionmentioning
confidence: 99%